A critical review on the formation, fate and degradation of the persistent organic pollutant hexachlorocyclohexane in water systems and waste streams. (May 2021) - Adithya, Srikanth; Jayaraman, Ramesh Sai; Krishnan, Abhishek; Malolan, Rajagopal; Gopinath, Kannappan Panchamoorthy; Arun, Jayaseelan; Kim, Woong; Govarthanan, Muthusamy
Abstract: The environmental impacts of persistent organic pollutants (POPs) is an increasingly prominent topic in the scientific community. POPs are stable chemicals that are accumulated in living beings and can act as endocrine disruptors or carcinogens on prolonged exposure. Although efforts have been taken to minimize or ban the use of certain POPs, their use is still widespread due to their importance in several industries. As a result, it is imperative that POPs in the ecosystem are degraded efficiently and safely in order to avoid long-lasting environmental damage. This review focuses on the degradation techniques of hexachlorocyclohexane (HCH), a pollutant that has strong adverse effects on a variety of organisms. Different technologies such as adsorption, bioremediation and advanced oxidation process have been critically analyzed in this study. All 3 techniques have exhibited near complete removal of HCH under ideal conditions, and the median removal efficiency values for adsorption, bioremediation and advanced oxidation process were found to be 80%, 93% and 82% respectively. However, it must be noted that there is no ideal HCH removal technique and the selection of removal method depends on several factors. Furthermore, the fates of HCH in the environment and challenges faced by HCH degradation have also been explained in this study. The future scope for research in this field has also received attention. Highlights: HCH affects endocrine receptors, immune and reproductive systems of human. Transportation of HCH occurs through rain water run off to water bodies. HCH is reported to be present in breast milk of human. Adsorption, AOP and Biodegradation are the methods used to remove HCH. Biodegradation by consortia is economical and efficient for source reduction.